Causal Relationship between Creativity-Oriented Intrinsic Motivation and Creative Achievements: Mediated by Mediation of Self-Actualization - Omolbanin Sheibani; Alireza Haji Yakhchali; Gholam Hossein Maktabi; Naser Behroozi (Iranian Evolutionary Educational Psychology Journal)
Objective: The present study aimed to test and compare the causal relationship between creativity-oriented intrinsic motivation and creative achievements with the mediation of self-actualization in male and female secondary school students of Yazd city. Methods: The statistical encompassed all male and female second-grade students in Yazd city during the academic year 2023. Through the multi-stage random sampling technique, 340 individuals were chosen as the sample for hypothesis testing. Research variables were assessed using various questionnaires such as Creative achievement questionnaires (Carson et al., 2005), Dynamic mental attitude questionnaire (Karwowski et al., 2014), Creative effectiveness questionnaire (Karwowski et al., 2012), Creative intrinsic motivation scale (Taylor & Kaufman, 2021) and Ahvaz self-actualization questionnaire (IsmailKhani et al., 2010). Data analysis was conducted using the Structural Equation Modeling approach and AMOS software. Results: The outcomes indicated that the proposed model fits well. The findings revealed that the indirect relationship between dynamic mental attitude, creative effectiveness, creative personal identity and creative inner motivation with creative writing, invention and scientific discovery through self-actualization is significant, with path coefficients ranging from β=0.14 to β=0.31, all statistically significant (p < 0.001). Moreover, the standard coefficients of the path between self-actualization and invention in this model for male students is β=0.15, while for girls it is β=0.08. Therefore, the difference of this path in the two groups is confirmed in favor of male students. Conclusions: Overall, it can be concluded that motivation oriented towards creativity can enhance students' creative accomplishments through the mechanism of self-realization.